Energy Storage, Lasered!: In the production equipment for lithium‐ion batteries, laser processes are becoming increasingly important. Issue 4 (1st August 2019) - Wegener, Maximilian
Abstract: Lithium‐ion batteries are a key technology for all automotive manufacturers in 2019. The broad market acceptance of battery‐powered mobility is dependent primarily on three factors: greater capacity with higher charging and discharging currents for a long range and short charging times, absolute safety, and declining production costs. As a technologically leading manufacturer of fully integrated production lines for lithium‐ion batteries, high‐tech equipment manufacturer Manz is thus focused on the advantages of laser process technology.